FIBRODYSPLASIA (MYOSITIS) OSSIFICANS PROGRESSIVA: TWO CASES REPORT - Sibel Özbudak Demir; Göknur Karahan; Gülümser Aydın; Füsun Köseoğlu (Archives of Rheumatology, 2001)
Fibrodysplasia (myositis) ossificans progresiva (FOP) is a hereditary mesodermal tissue characterized by progressive ossification of striated muscle, tendon, ligament, fasciae, aponeurose and occasionally skin. The pattern of inheritance remains unknown. Indeed, most reported cases are the result of spontaneous mutations. In this article we present two cases with FOP and reviewed the literature.